The need for a multicultural approach to mathematics curriculum design for the senior secondary school phase: a case study conducted at the Woolhope Secondary School, Port Elizabeth - Govender, Vasuthavan Gopaul (Rhodes University, Faculty of Education, Department of Education, 1994)
Multicultural countries such as England have recognised the need to multiculturalise their mathematics curricula to cater for the needs of all ethnic/cultural groups, to encourage racial harmony and have pupils of a specific culture learn about, and accord respect to, another culture (Duncan, 1986;Dyson, 1986; Gilbert, 1984). However, in South Africa, a multicultural country with its large Black majority, such an approach has not been given the necessary attention. Laridon (1990) has criticised the way in which curriculum development in mathematics is conducted in South Africa. He describes it as a "top-down" approach and based on input from non-representative samples of teachers and not taking into account the needs of all cultural groups in South Africa. He criticises the manner in which topics are added to or removed from the syllabus and calls this "syllabus tinkering". With a number of, mostly English medium, schools opening their doors to all races, it is possible that certain cultural groups are at a disadvantage when compared with others if modifications to the syllabus, to accommodate their needs, are not made. This study is a small scale case-study, conducted at Woolhope Secondary, a predominantly Indian school, but with a significant number of Black pupils (approximately 25%). The study focusses on the need for a multicultural approach to mathematics curriculum design. The views of the senior mathematics pupils and mathematics teachers are considered in this regard, and together with the relevant literature, broad guidelines for a multicultural mathematics curriculum design in South Africa are suggested.
Keywords: Mathematics -- Curricula -- South Africa -- Case studies; Multicultural education -- South Africa -- Case studies; Education, Secondary -- Research -- South Africa